2016
DOI: 10.1186/s12889-016-3434-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hardcore smoking in the Netherlands between 2001 and 2012: a test of the hardening hypothesis

Abstract: BackgroundHardcore smokers are smokers who have smoked for many years and who do not intend to quit smoking. The “hardening hypothesis” states that light smokers are more likely to quit smoking than heavy smokers (such as hardcore smokers). Therefore, the prevalence of hardcore smoking among smokers would increase over time. If this is true, the smoking population would become harder to reach with tobacco control measures. In this study we tested the hardening hypothesis.MethodsWe calculated the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Most tests of the hardening hypothesis have examined changes over time in the prevalence of hardcore behaviours (‘hardening indicators’),6–9 or correlations between smoking prevalence and the prevalence of hardening indicators 4 10. Common hardening indicators include measures of nicotine dependence and quitting intent and activity 4 11 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most tests of the hardening hypothesis have examined changes over time in the prevalence of hardcore behaviours (‘hardening indicators’),6–9 or correlations between smoking prevalence and the prevalence of hardening indicators 4 10. Common hardening indicators include measures of nicotine dependence and quitting intent and activity 4 11 12.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, most evidence to date does not support the hardening hypothesis. Hardcore smokers comprise a minority of smokers,11 and research in the USA,6 8 9 New Zealand3 and Europe7 8 13 consistently finds either no change in hardening indicators or even a ‘softening’ of the smoking population. Australian studies have similarly found no evidence of hardening among smokers overall 14 15…”
Section: Introductionmentioning
confidence: 99%
“…For example, while a US study reported softening occurred among high but not low SES smokers, 4 a Dutch study found similar levels of softening over time by education level. 12 A New Zealand study reported little evidence for hardening, with similar findings for Māori (indigenous peoples of New Zealand) and non-Māori smokers. 13 Studies from California have found similar degrees of softening among smokers with varying levels of psychological distress and from different ethnic populations.…”
Section: Richard Edwardsmentioning
confidence: 90%
“…Investigations from a variety of countries have generally found little or no evidence in support of the hypothesis. [1][2][3][4][5][6][7][8][9][10][11][12][13] The study reported in this edition of the journal by Brennan and colleagues adds to this (lack of) evidence through a rigorous analysis of repeated cross-sectional surveys in Victoria, Australia between 2001 and 2015. 14 Strengths of the study include the long time period investigated, the wide range of hardening indicators studied, an analysis of hardening within demographic subgroups and sensitivity analyses of the findings.…”
Section: Richard Edwardsmentioning
confidence: 99%
“…Hardcore smokers are people who have smoked for many years and have no intention-toquit smoking (Costa et al, 2010). In 2012, 32% of Dutch smokers could be considered 'hardcore', which equals to 8% of the Dutch general population (Bommel e et al, 2016). Compared to non-hardcore smokers, they have lower quitting self-efficacy (Sorg, Xu, Doppalapudi, Shelton, & Harris, 2011) and tend to have dysfunctional beliefs about smoking (Bommel e et al, 2014).…”
Section: Statement Of Contributionmentioning
confidence: 99%